Examining the Influence of Alexithymia, Gender, and Age on Drug Use among Iranian Students: the Mediating Role of Emotion Regulation Difficulties - Mohamad Hatami Nejad; Masoud Sadeghi; Esmaeil Sadri Damirchi; Mohammadreza Noroozi Homayoon (Scientific Reports)
Abstract The objective of the present study was to predict drug use among Iranian students on the basis of alexithymia, gender, age, and the mediating role of emotion regulation difficulty. This research employed a descriptive-correlational approach (structural equation modeling). The statistical population included 400 high school students studying during the 2023–2024 academic year in the cities of Khorramabad and Ardabil. The instruments used in this study included the short form of the Difficulties in Emotion Regulation Scale (DERS-SF), the Toronto Alexithymia Scale (TAS-20), and the Addiction Potential Scale (APS) in its Iranian version. The path coefficients related to the effect of alexithymia and the mediating role of emotion regulation difficulty were significant at the 0.05 level, except for the paths from gender and age to drug use tendency, which were not confirmed. Age, gender, and alexithymia collectively explained 52% of the variance in emotion regulation difficulty, whereas emotion regulation difficulty, age, gender, and alexithymia explained 46% of the variance in drug use propensity among students. Among the variables studied, only age and gender were not significant predictors of drug use in Iranian students, whereas alexithymia, both directly and through the mediating role of emotion regulation difficulty, significantly predicted drug use propensity.